Seasonal Variation in Rates of Dust Fall at Motor Parks of University of Ilorin, Ilorin, Nigeria - Nwosu, F. O.; Olayinka, O. D.; Akoshile, C. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The enormous vehicular activities on the commercial motor parks of University of Ilorin, Nigeria called for concern as a result of noticeable level of particulate matter in the atmosphere of the area. This study was carried out to indicate the seasonal variation in the rate of dust fall at three motor parks in the permanent site of the University campus by using the single bucket sampling method. The study was carried out for five months each of wet and dry season periods. The sampling sites were First Motor Park (PK1), New Motor Park (PK2) and Clinic Area (Cl). Gravimetric method was used to quantify the soluble, insoluble, volatile matter and ash content of the dust. Volatile matter and ash were the component of insoluble dust and the highest rate of insoluble dust deposition was observed in January (2043.12 ± 41.4 and 284.1 ± 35.5 mg/m2/day) for PK2 and Cl and in November (1282.7 ± 64.9 mg/m2/day) for PK1 when their respective traffic density (1509.5 ±72.1, 29.8 ± 1.2 and 1000.8 ± 48.3 vehicles per hour) was highest. The highest (32713.0 ± 1290.1 mg/m2/day) and lowest (70.6 ± 6.9 mg/m2/day) rate of soluble dust deposition in the study were observed at PK1 for September and February respectively which was suspected to be due to increase and decrease in the amount of rain fall. The Pearson Correlation showed that increases in traffic density were correlated with increases in the rate of insoluble dust fall at various sites and the relationship was in the stronger order of PK2 > PK1 > Cl. The motor parks ambient air was highly contaminated with soluble dust in the wet season and insoluble dust in the dry season their being values are more than the recommended 133 mg/m2/day.